More meaningful education - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
CTA sponsored a study visit by eleven senior African agricultural trainers who are involved in or have influence on agricultural education and training in their countries. The participants came from Ghana, Malawi, Mauritius, Namibia, Nigeria, Tanzania, Za